Investigation of the Effect of Some Parameters Affecting the Sleep Quality of Sports-Trained Students - Gamze Güney, Osman Imamoğlu, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to investigate the effect of some parameters affecting the sleep quality of sports-trained students. Methods: For this purpose, the Pittsburgh sleep quality scale was applied to sports-trained students. The data of 243 male and 222 female students who completed the scale truthfully were evaluated. Student t-test, one-way ANOVA, and LSD tests were used in statistical procedures. Results: A statistically significant difference was found in the subcomponents and total sleep scores of subjective sleep quality, habitual sleep efficiency, sleep latency, sleep duration, sleep disturbance, medication use, and daytime dysfunction by gender (p<0.05 and p<0.001). There was no statistically significant difference in subjective sleep quality, sleep latency, sleep duration, sleep disturbance, daytime dysfunction, and total sleep scores with regard to team and individual sports (p>0.05). There was a statistically significant difference in subjective sleep quality, sleep latency, sleep duration, medication use, daytime dysfunction, and total sleep score with regard to daily training time (p<0.05 and p<0.001). The difference is not significant in the subcomponents of habitual sleep efficiency and sleep disturbance (p>0.05). Conclusion: It was concluded that while gender has an effect on the sleep quality of sports-trained students, playing team and individual sports have not. In addition, it has been observed that more than 3 hours of daily training time has a negative effect on sleep quality. It is recommended that sports-trained students who train intensively should be supported in terms of sleep quality, especially female students.